Including forestry in an emissions trading scheme: Lessons from New Zealand - Carver, Thomas; Dawson, Patrick; O’Brien, Sophie; Kotula, Hannah; Kerr, Suzi; Leining, Catherine (Frontiers in Forests and Global Change, 2022)
The forestry sector has a crucial role to play in mitigating climate change. Given the share of global emissions covered by emissions trading is expected to rise, there is a need to understand how emissions trading might drive behavior change in the forestry sector. To explore this, we analyze the New Zealand Emissions Trading Scheme (NZ ETS) − the only system in the world with symmetrical incentives that reward forest owners who afforest and make liable those who deforest. In theory, these incentives should drive net carbon dioxide removals in the forestry sector, but the sectoral response has proven complex. We evaluate the NZ ETS policies that directly affect forestry and the sectoral response to these policies by analyzing trends in deforestation, afforestation, and participation over 2008 to 2022. Our findings indicate that the forestry sector, and the NZ ETS participants within it, have responded rationally to emissions pricing over time. However, multiple factors such as complex participation requirements, extended periods of policy uncertainty, and weak emissions price signals (particularly over 2011–2016) have likely restricted the effectiveness of the NZ ETS in changing forestry outcomes over much of its operating life. The Climate Change Response (Emissions Trading Reform) Amendment Act, 2020 reformed forestry and other provisions in the NZ ETS to address demonstrated shortcomings, improve policy predictability, and incentivize more ambitious mitigation action in line with Aotearoa New Zealand’s targets. However, the signaling of further changes to NZ ETS forestry policy in 2022 has created new uncertainty for market participants. Despite past challenges, the sector’s dramatic response to rising emissions prices in recent years demonstrates the NZ ETS is changing landowner behavior to produce net forestry removals. The NZ ETS remains a unique and strong model from which other nations can gain insights in how to design and operate emissions trading systems to harness mitigation potential from the forestry sector and help meet their emission reduction targets.